Influence of sociodemographic and neighbourhood factors on self rated health and quality of life in rural communities: findings from the Agriproject in the Republic of Ireland. Issue 11 (13th October 2004) - Tay, Joseph B; Kelleher, Cecily C; Hope, Ann; Barry, Margaret; Gabhainn, Saoirse Nic; Sixsmith, Jane
Abstract : Objective: To examine the influence of sociodemographic and neighbourhood factors on self rated health, quality of life, and perceived opportunities for change (as one measure of empowerment) in rural Irish communities. Design: Pooled data from cross sectional surveys two years apart. Setting: Respondents in four randomly selected rural district electoral divisions with a population size of between 750 and 2000. Participants: 1738 rural dwellers aged 15–93, 40.5% men, interviewed at two time points. Main outcome measures: Determinants of self rated health (SRH), quality of life (QOL), and perceived opportunities for change, rated on a closed option Likert scale and assessed in multivariate logistic regression models. Main results: Overall 23.8% of the sample reported poor SRH, 22.2% poor QOL, and 50.1% low perceived opportunities for change. Low financial security and dissatisfaction with work were each significantly associated with poor SRH (OR = 1.96 (1.50 to 2.56) and 1.54 (1.11 to 2.14)), with poor QOL (OR = 2.04 (1.56 to 2.68) and 1.87 (1.34 to 2.61). Concern about access to public services was significantly predictive of SRH (OR = 1.47 (1.11 to 1.94)) rather than access to health care (that is, hospital and GP services). There were distinct sex specific patterns and a generational effect for educational status in men. Variables associated with social networks and social support were less strongly predictive of SRH and QOL when economic measures were accounted for. Conclusion: Inter-relations between indicators of health status, wellbeing, and deprivation are not well studied in rural communities. Material deprivation has a direct influence on both health status and quality of life, although immediate sources of support are relatively well preserved.